Reequilíbrio econômico-financeiro de contratos de concessão de serviços de transmissão: estudo de casos - Regis, Vládia Viana (2017)
The present study aims to analyze the economic and financial imbalance of electric power transmission service concession contracts by studying cases attached to the materialization of three risks: (1) the environmental risk, (2) the risk of unilateral modifications of the contract in the case of enhancements and improvements, and (3) the regulatory risk embodied in the Provisional Measure 579/2012. For this purpose, the legal framework that shapes the structure of the national electricity sector will be analyzed through the investigation of the electricity sector restructuring promoted since the Constitution of 1988, with a special focus on the vertical unbundling of services, the delegation model adopted for transmission services, the operation of the Brazilian Electricity Regulatory Agency (ANEEL) in the energy transmission sector as well as on the tariff regulation regime adopted. This study will also examine the application of the theory of risk sharing to concession contracts and its specific risks, in order to, finally, expose conclusions about the impacts of the three selected risks on the economic and financial balance of the contracts and on the stability of the market, presenting solutions and proposals within the review of these three cases